(untitled) (Journal of Economic Research & Business Administration, 2024)
Quality of life is a multifaceted concept that reflects the level of well-being and life satisfaction of the population. President K.K. Tokayev noted that ‘in order to improve the quality of life of every Kazakhstani citizen, infrastructural issues that directly affect the quality of life will be in the centre of attention’. Indicators of the quality of life of the population are important indicators for assessing the specific socio-economic consequences of the ongoing transformations and the degree of social tension in society. Therefore, the quality of life of the population becomes relevant in the centre of attention of the state leadership. The purpose of the article is to determine the actual assessment criteria for Kazakhstan and to propose measures to improve the quality of life in the conditions of globalisation and modernisation. An analysis is conducted based on existing approaches to assessing the quality of life and similar concepts of sustainable development. It is considered how improving the quality of life can contribute to the development of regions in the context of globalization and economic modernization, paying special attention to promoting sustainable development. This article examines the relationship between economic growth and population well-being in Kazakhstan. It examines the dynamics of gross domestic product (GDP), the state of education and proposes measures to improve the education system in the country. The importance of cooperation between the government, business and the public in the implementation of these strategies is emphasized. Promoting and implementing these strategies requires open dialogue, support for project development efforts and attention to every aspect of development. These efforts will contribute to a stable and uniform improvement in the quality of life of the population of Kazakhstan and the region as a whole. Key words: quality of life, factors, sustainable development, welfare, income.